Optical and Electrical Properties of Transition Metal Calcium Phosphate Glasses - Mohd Tarmizi, Emma Ziezie (2006)
Investigation was carried out between binary and ternary series in order to determine the role of transition metal (TM) ions in calcium phosphate glass. Various transition metal ions in calcium phosphate glass (TM0)y (Ca0)0.~(P~2-0~s) o.7(, TM = Cu, Mn and Zn) in the composition range 0.011x10.09 were prepared by traditional melt quenching technique. Optical absorption, dielectric spectroscopy, X-ray diffraction and Fourier Transform Infrared (FTIR) spectroscopy have been used to characterize the structural, optical and electrical features of the glasses. All of the samples under study have been confirmed to be amorphous by X-ray diffraction (XRD) measurements. Results from FTIR spectroscopy showed that the spectra were dominated by the spectral characteristic of P2O5 in a fingerprint region below 1500 cm". From the absorption edge studies, the values of optical band gap (EopJ and energy gap (E,) have been evaluated using Urbach absorbance rule. The values of optical band gap (Eop,) recorded for binary CaO-P205 glasses ranges from 3.578 to 2.1 14 eV while for ternary series CaO-P205 doped with Cu20, CuO, MnO and ZnO ranging from 2.1 14 to 1.697 eV, 3.310 to 1.718 eV, 3.030 to 3.279 and from 2.747 to 2.989 eV. Binary and ternary series doped with CU+ and ~ nsho~wed+ the energy gap, E, increased with metal oxide and dopant materials ranges from 0.500 to 1.564 eV, 0.681 to 0.736 eV and from 0.246 to 0.283 eV. CaO-P205 glasses doped with, cu2+ and zn2+ recorded inverse pattern where the values ranging from 1.863 to 0.600 eV and from 1.1 72 to 0.744 eV. Optical band gap (E,,,) and energy gap (E,) is suggested to be associated with structural disorder in the sample. A number of physical studies have also been conducted which include refractive index and density. The density of the glass was determined by Archimedes Principle. Refractive Index was determined at 589.3 nrn and 632.6 nrn and was found to agree with Lorentz-Lorenz equation where the refractive index increased with increase of density of the samples. Dielectric permittivity was measured in the temperature range of 25 to 300°C. Dielectric permittivity and dielectric loss factor for all samples decreased with frequency and increased with temperature between range 1 x 1 o3 to 1 Hz and from 1 x 10" to 1 x lop3 Hz. From the empirical data, other values such as molar volume and molar refractivity have been computed. Ionic refractivity, ionic radii and field strength have been interpreted from the obtained data. It is obvious that the refractive index varies with molar refractivity, which depends on the polarizability of the ions in the samples, density and molecular weight. Those properties were found to be sensitively depends on its compositions.